Effectiveness of Supply Chain Networks and Business Profitability: An Empirical Study - Saxena, Dr. Gaurav (International Journal of Advanced Science and Technology, 2020)
Supply Chain Networks important element of every business now a days. An effective supply chain management helps a business in number of ways, like it directly improves customer services, right product & right quantity can be delivered to customer in a timely &proper manner to satisfy both producer & customer. The purpose of this paper is to find how an effective supply chain management helps in the improving the profitability of an organization. A sample of 118 employees in which 60.17% male & 39.83% female has been considered through a standard questionnaire designed on five point interval scale. Mean & t-test have been applied to derive the result of the survey. It was observed from the result that an effective process of supply chain networks have a profitable effect on the business as well as on entrepreneur.